A PRISMA-compliant systematic review and meta-analysis of randomized controlled trials investigating the effects of statin therapy on plasma lipid concentrations in HIV-infected patients. (September 2016) - Banach, Maciej; Dinca, Madalina; Ursoniu, Sorin; Serban, Maria-Corina; Howard, George; Mikhailidis, Dimitri P.; Nicholls, Stephen; Lip, Gregory Y.H.; Glasser, Stephen; Martin, Seth S.; Muntner, Paul; Rysz, Jacek; et al.
Graphical abstract: Abstract: Statin therapy may lower plasma lipid concentrations, but the evidence in HIV-infected patients is still unclear. Therefore, we aimed to investigate the impact of statin therapy on plasma lipid concentrations through a systematic review of the literature and meta-analysis of available randomized controlled trials (RCTs). The literature search included PUBMED, SCOPUS, Web of Science and Google Scholar up to October 30, 2015. The meta-analysis was performed using either a fixed-effects or random-effect model according to I 2 statistic. Effect sizes were expressed as weighted mean difference (WMD) and 95% confidence interval (CI). Two investigators independently reviewed the title or abstract, further reviewed the full-texts and extracted information on study characteristics and study outcomes. Meta-analysis of 12 RCTs with 697 participants suggested significant reductions in plasma concentrations of low density lipoprotein (LDL) cholesterol (WMD: ⿿0.72 mmol/L [⿿27.8 mg/dL], 95%CI: ⿿1.04, ⿿0.39, p  < 0.001; I 2  = 85.7%), total cholesterol (WMD: ⿿1.03 mmol/L [-39.8 mg/dL], 95%CI: ⿿1.42, ⿿0.64, p  < 0.001; I 2  = 94.7%) and non-high density lipoprotein cholesterol (non-HDL-C) (WMD: ⿿0.81 mmol/L [⿿31.3 mg/dl], 95%CI: ⿿1.32, ⿿0.30, p  = 0.002; I 2  = 76.5%), and elevations in HDL-C (WMD: 0.072 mmol/L [2.8 mg/dL], 95%CI: 0.053, 0.092, p  < 0.001; I 2  = 0%) following treatment with statins (mostly of moderate-intensity). No significant alteration in plasma triglycerides (TG) concentrations was found (WMD: ⿿0.16 mmol/L [⿿14.2 mg/dL], 95%CI: ⿿0.61, 0.29, p  = 0.475; I 2  = 90.2%). All these effects were robust in sensitivity analysis, suggesting that the computed effect is not driven by any single study. In subgroup analysis, no significant difference was found among different statins in terms of changing plasma concentrations of LDL-C, HDL-C and TG. However, atorvastatin was found to be more efficacious in reducing plasma total cholesterol concentrations ( p  < 0.001). In conclusion, the meta-analysis suggested significant reductions in plasma concentrations of LDL-C, total cholesterol and non-HDL-C, and elevations in HDL-C, but no significant alteration in plasma TG following treatment with statins.